High-strength flame-retardant polyurethane structural adhesive for new energy lithium battery and preparation method of high-strength flame-retardant polyurethane structural adhesive
By using raw materials such as DOPO and magnesium hydroxide, high-strength flame-retardant polyurethane structural glue was prepared, which solved the problem of insufficient flame retardant performance and strength of polyurethane structural glue for lithium batteries, and achieved excellent flame retardant performance, mechanical properties and safety of lithium batteries.
Patent Information
- Application Number
- CN202510261135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-06
AI Technical Summary
At this stage, the flame retardant properties and strength of polyurethane structural adhesives for lithium batteries are insufficient, resulting in the lithium batteries being easily burned or exploded in abuse or accidents, affecting safety.
High-strength flame retardant polyurethane structural glue is prepared through specific reaction steps and process methods using raw materials such as 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide (DOPO) and magnesium hydroxide. The structural glue consists of castor oil, polyether polyol, polyester polyol, plasticizer, chain extender, dibutyltin dilaurate, phosphorus-containing modified magnesium hydroxide and phosphorus-containing diisocyanate, and is prepared by ultrasonic dispersion, planetary stirring and thermal reaction.
The prepared high-strength flame-retardant polyurethane structural adhesive exhibits excellent flame retardant properties, mechanical properties and peel strength, which can effectively improve the safety and service life of lithium batteries.
Smart Images

Figure CN119775952A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane structural adhesives, in particular to a high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries and a preparation method thereof. Background Art
[0002] Due to the rapid development of new energy vehicles, new energy lithium batteries are one of the most critical components of new energy vehicles. As a power source, they directly affect the performance of new energy vehicles such as cruising range, safety, and service life. Structural adhesives are an indispensable part of lithium batteries. At present, lithium batteries will burn or even explode if abused, which affects people's life and property safety to a certain extent. Structural adhesives can provide safety and reliability to a certain extent. Therefore, improving the flame retardant properties of structural adhesives for lithium batteries is a hot topic for current researchers.
[0003] In the molecular structure of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), there is an active hydrogen on the phosphorus, which can react with unsaturated compounds to generate a series of derivatives. The phosphaphenanthrene structure is introduced into the compound, so that the new compound exhibits excellent flame retardant properties. The present invention uses DOPO and raw materials such as magnesium hydroxide to prepare a high-strength flame-retardant polyurethane structural adhesive, which can solve the poor flame retardant properties and poor strength of polyurethane structural adhesives for lithium batteries at this stage, and has very important application value in the field of new energy lithium batteries. Summary of the invention
[0004] The purpose of the present invention is to overcome one or more deficiencies in the prior art and provide a high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries. The polyurethane structural adhesive prepared by the method has been verified to have excellent flame retardant properties and mechanical properties through experiments.
[0005] In order to achieve the above object, a technical solution adopted by the present invention is: A high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries, the polyurethane structural adhesive is composed of the following raw materials in parts by weight: 100 parts by weight of castor oil, 10-30 parts of polyether polyol, 10-30 parts of polyester polyol, 10-20 parts of plasticizer, 2-4 parts of chain extender, 1-3 parts of dibutyltin dilaurate, 10-30 parts of phosphorus-modified magnesium hydroxide, and 10-30 parts of phosphorus-containing diisocyanate; The preparation method of the polyurethane structural adhesive is: S1. Under a nitrogen atmosphere, add dried ultrafine magnesium hydroxide and phosphorus-containing diisocyanate to a toluene solvent, disperse by ultrasonication, heat to 80-90°C, stir and react for 6-10 hours. After the reaction is completed, cool to room temperature, wash with toluene, and dry to obtain phosphorus-containing modified magnesium hydroxide; S2. Add castor oil, polyether polyol, polyester polyol and plasticizer into a planetary mixer, dehydrate at 120°C for 3 hours, cool to 50°C, add chain extender, dibutyltin dilaurate and phosphorus-modified magnesium hydroxide, mix evenly, heat to 70-80°C, react for 2-4 hours, finally add phosphorus-containing diisocyanate, stir and mix evenly to obtain high-strength flame-retardant polyurethane structural adhesive.
[0006] Preferably, in S1, the mass amount of phosphorus-containing diisocyanate is 1.5-3 times the mass amount of ultrafine magnesium hydroxide.
[0007] Preferably, the preparation method of the phosphorus-containing diisocyanate is: (1) Add iminodipropionic acid and 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add diphenylphosphine chloride, add triethylamine under nitrogen protection, stir and disperse, heat to 70-80°C, react for 20-35h, and after the reaction, wash with deionized water, dry, filter, and rotary evaporate to obtain intermediate 1; (2) Under nitrogen protection, the intermediate product 1, epoxybutene and tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 80-90°C, reacted for 24-30 hours, and after the reaction was completed, vacuum distilled, washed with deionized water, and dried to obtain the intermediate product 2; (3) Add DOPO to toluene solvent, stir to dissolve, then add intermediate product 2, heat to 100-120°C, react for 6-10 hours, and after the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3; (4) The intermediate product 3 and isophorone diisocyanate are added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 60-75° C., and dibutyltin dilaurate is added thereto. The reaction is carried out for 3-6 hours. After the reaction is completed, the product is distilled under reduced pressure, washed with deionized water, and dried to obtain phosphorus-containing diisocyanate.
[0008] More preferably, in (1), the molar ratio of iminodipropionic acid to diphenylphosphinyl chloride is 1:1-1.2.
[0009] More preferably, in (2), the molar ratio of the intermediate product 1 to epoxybutene is 1:2-2.4.
[0010] More preferably, in (3), the molar ratio of DOPO to the intermediate 2 is 2-2.5:1.
[0011] More preferably, in (4), the molar ratio of the intermediate product 3 to isophorone diisocyanate is 1:2.2-2.5.
[0012] The reaction mechanism of the present invention is as follows: the present invention utilizes iminodipropionic acid and diphenylphosphine chloride to obtain an intermediate product 1 through a substitution reaction under the catalysis of 4-dimethylaminopyridine, utilizes the carboxyl structure contained therein to carry out a ring-opening reaction with epoxybutene to obtain an intermediate product 2, and then carries out an addition reaction with DOPO to obtain an intermediate product 3, and reacts with isophorone diisocyanate under the initiation catalysis of dibutyltin dilaurate to obtain a phosphorus-containing diisocyanate, and finally mixes it with castor oil, polyether polyol, polyester polyol, plasticizer, etc. to obtain a high-strength flame-retardant polyurethane structural adhesive.
[0013] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: 1. Magnesium hydroxide is an inorganic material, and its surface contains a large amount of hydroxyl groups, so it is very easy to reunite and difficult to disperse in an organic matrix. The present invention reacts it with phosphorus-containing diisocyanate, and the hydroxyl groups on the surface of magnesium hydroxide are used to react with the -NCO groups in the phosphorus-containing diisocyanate to form carbamate, which is organicized to increase its compatibility with organic substances, and is evenly dispersed in the organic matrix. The formed carbamate is used to form hydrogen bonds with other polar groups such as carbamate groups, isocyanate groups, ester groups and other strong polar groups, and more cross-linking sites are generated. When subjected to external force, magnesium hydroxide can not only serve as a stress concentration point, absorbing more external forces, but also, the cross-linked network structure thus formed can also absorb and disperse more external forces, and further improve the mechanical properties of the structural adhesive. In addition, since the structure prepared by the present invention contains more polar groups, it can produce stronger chemical links such as hydrogen bonds with the surface of the coated substrate, thereby improving the peel strength of the structural adhesive.
[0014] 2. Magnesium hydroxide is an excellent inorganic flame retardant, which can decompose and dehydrate at high temperature, reduce the temperature of the base material by decomposing and absorbing heat, and the water vapor produced by high-temperature decomposition can form a water vapor film on the surface of the base material to isolate external oxygen. In addition, a layer of non-flammable oxides will be formed, attached to the surface of the base material, and introduced into the structural adhesive, which can effectively improve the flame retardant properties of the structural adhesive. The structural adhesive prepared by the present invention also has a large number of phosphorus-containing structures, which can produce strong acidic substances by thermal decomposition, have a strong dehydration effect, promote material carbonization, and form a dense carbon layer on the surface of the base material, which hinders the transport of materials and the transfer of energy, and forms an organic-inorganic flame retardant structure with magnesium hydroxide, and the two are synergistically flame retardant, and jointly improve the flame retardant properties of the material. The structural adhesive prepared by the present invention has been confirmed to have excellent flame retardant effect, mechanical properties and peel strength through experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the reaction route of phosphorus-containing diisocyanates. DETAILED DESCRIPTION
[0016] The following is a further detailed description of the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries and its preparation method in conjunction with specific embodiments. These embodiments are only used for comparison and explanation purposes, and the present invention is not limited to these embodiments.
[0017] Example 1: (1) Add 0.1 mol of iminodipropionic acid and 1 mmol of 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add 0.12 mol of diphenylphosphinoyl chloride, add 0.01 mol of triethylamine under nitrogen protection, stir and disperse, heat to 75°C, react for 35 hours, and after the reaction, wash with deionized water, dry, filter, and rotary evaporate to obtain intermediate 1.
[0018] (2) Under nitrogen protection, 80 mmol of intermediate product 1, 170 mmol of epoxybutene and 1.2 mmol of tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 85°C, and reacted for 30 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed with deionized water, and dried to obtain intermediate product 2.
[0019] (3) Add 70 mmol of DOPO to toluene solvent, stir to dissolve, then add 30 mmol of intermediate product 2, heat to 110°C, react for 8 h. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3.
[0020] (4) Add 80 mmol of the intermediate product 3 and 200 mmol of isophorone diisocyanate to N,N-dimethylformamide solvent, stir and mix evenly, heat to 65°C, add 0.8 mmol of dibutyltin dilaurate, react for 3 h, and after the reaction is completed, distill under reduced pressure, wash with deionized water, and dry to obtain phosphorus-containing diisocyanate.
[0021] (5) Under a nitrogen atmosphere, 4 g of dry ultrafine magnesium hydroxide and 6 g of phosphorus-containing diisocyanate were added to a toluene solvent, dispersed by ultrasonication, heated to 85°C, and stirred for reaction for 10 h. After the reaction was completed, the mixture was cooled to room temperature, washed with toluene, and dried to obtain phosphorus-containing modified magnesium hydroxide.
[0022] (6) Add 50 g of castor oil, 5 g of polyether polyol (PPG400), 10 g of polyester polyol (PBA-3000), and 8 g of plasticizer DIDP into a planetary mixer, dehydrate at 120 °C for 3 h, cool to 50 °C, add 1 g of chain extender BDO, 1.5 g of dibutyltin dilaurate, and 5 g of phosphorus-modified magnesium hydroxide, mix well, heat to 75 °C, react for 4 h, and finally add 10 g of phosphorus-containing diisocyanate and stir to mix well to obtain a high-strength flame-retardant polyurethane structural adhesive.
[0023] Example 2: (1) Add 0.1 mol of iminodipropionic acid and 1.2 mmol of 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add 0.12 mol of diphenylphosphinoyl chloride, add 0.08 mol of triethylamine under nitrogen protection, stir and disperse, heat to 70°C, react for 35 hours, and after the reaction, wash with deionized water, dry, filter, and evaporate to obtain intermediate 1.
[0024] (2) Under nitrogen protection, 80 mmol of intermediate product 1, 192 mmol of epoxybutene and 1 mmol of tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 85°C, and reacted for 25 h. After the reaction was completed, vacuum distillation was performed, the mixture was washed with deionized water, and dried to obtain intermediate product 2.
[0025] (3) Add 75 mmol of DOPO to toluene solvent, stir to dissolve, then add 30 mmol of intermediate product 2, heat to 115°C, react for 10 h. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3.
[0026] (4) Add 80 mmol of the intermediate product 3 and 180 mmol of isophorone diisocyanate to N,N-dimethylformamide solvent, stir and mix evenly, heat to 75°C, add 0.5 mmol of dibutyltin dilaurate, and react for 6 hours. After the reaction is completed, distill under reduced pressure, wash with deionized water, and dry to obtain phosphorus-containing diisocyanate.
[0027] (5) Under a nitrogen atmosphere, 4 g of dry ultrafine magnesium hydroxide and 8 g of phosphorus-containing diisocyanate were added to a toluene solvent, dispersed by ultrasonication, heated to 85°C, and stirred for reaction for 10 h. After the reaction was completed, the mixture was cooled to room temperature, washed with toluene, and dried to obtain phosphorus-containing modified magnesium hydroxide.
[0028] (6) Add 50 g of castor oil, 10 g of polyether polyol (PPG400), 15 g of polyester polyol (PBA-3000), and 10 g of plasticizer DIDP into a planetary mixer, dehydrate at 120 °C for 3 h, cool to 50 °C, add 2 g of chain extender BDO, 1 g of dibutyltin dilaurate, and 8 g of phosphorus-modified magnesium hydroxide, mix well, heat to 80 °C, react for 2 h, and finally add 12 g of phosphorus-containing diisocyanate and stir to mix well to obtain a high-strength flame-retardant polyurethane structural adhesive.
[0029] Example 3: (1) Add 0.1 mol of iminodipropionic acid and 1.5 mmol of 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add 0.1 mol of diphenylphosphinoyl chloride, add 0.012 mol of triethylamine under nitrogen protection, stir and disperse, heat to 80°C, react for 20 hours, and after the reaction, wash with deionized water, dry, filter, and rotary evaporate to obtain intermediate 1.
[0030] (2) Under nitrogen protection, 80 mmol of intermediate product 1, 160 mmol of epoxybutene and 1.4 mmol of tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 85°C, and reacted for 30 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed with deionized water, and dried to obtain intermediate product 2.
[0031] (3) Add 75 mmol of DOPO to toluene solvent, stir to dissolve, then add 30 mmol of intermediate product 2, heat to 120°C, react for 6 h. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3.
[0032] (4) Add 80 mmol of the intermediate product 3 and 176 mmol of isophorone diisocyanate to N,N-dimethylformamide solvent, stir and mix evenly, heat to 60°C, add 0.6 mmol of dibutyltin dilaurate, and react for 4 hours. After the reaction is completed, distill under reduced pressure, wash with deionized water, and dry to obtain phosphorus-containing diisocyanate.
[0033] (5) Under a nitrogen atmosphere, 4 g of dry ultrafine magnesium hydroxide and 10 g of phosphorus-containing diisocyanate were added to a toluene solvent, dispersed by ultrasonication, heated to 90°C, and stirred for reaction for 6 h. After the reaction was completed, the mixture was cooled to room temperature, washed with toluene, and dried to obtain phosphorus-modified magnesium hydroxide.
[0034] (6) Add 50 g of castor oil, 8 g of polyether polyol (PPG400), 12 g of polyester polyol (PBA-3000), and 10 g of plasticizer DIDP into a planetary mixer, dehydrate at 120 °C for 3 h, cool to 50 °C, add 1.5 g of chain extender BDO, 0.5 g of dibutyltin dilaurate, and 5 g of phosphorus-modified magnesium hydroxide, mix well, heat to 70 °C, react for 3 h, and finally add 15 g of phosphorus-containing diisocyanate and stir to mix well to obtain a high-strength flame-retardant polyurethane structural adhesive.
[0035] Example 4: (1) Add 0.1 mol of iminodipropionic acid and 1.2 mmol of 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add 0.12 mol of diphenylphosphinoyl chloride, add 0.01 mol of triethylamine under nitrogen protection, stir and disperse, heat to 80°C, react for 24 hours, and after the reaction, wash with deionized water, dry, filter, and rotary evaporate to obtain intermediate 1.
[0036] (2) Under nitrogen protection, 80 mmol of intermediate product 1, 180 mmol of epoxybutene and 1 mmol of tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 80°C, and reacted for 26 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed with deionized water, and dried to obtain intermediate product 2.
[0037] (3) Add 70 mmol of DOPO to toluene solvent, stir to dissolve, then add 30 mmol of intermediate product 2, heat to 100 °C, react for 10 h. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3.
[0038] (4) Add 80 mmol of the intermediate product 3 and 180 mmol of isophorone diisocyanate to N,N-dimethylformamide solvent, stir and mix evenly, heat to 65°C, add 0.6 mmol of dibutyltin dilaurate, and react for 5 h. After the reaction is completed, distill under reduced pressure, wash with deionized water, and dry to obtain phosphorus-containing diisocyanate.
[0039] (5) Under a nitrogen atmosphere, 4 g of dry ultrafine magnesium hydroxide and 12 g of phosphorus-containing diisocyanate were added to a toluene solvent, dispersed by ultrasonication, heated to 85°C, and stirred for reaction for 8 h. After the reaction was completed, the mixture was cooled to room temperature, washed with toluene, and dried to obtain phosphorus-modified magnesium hydroxide.
[0040] (6) Add 50 g of castor oil, 15 g of polyether polyol (PPG400), 5 g of polyester polyol (PBA-3000), and 5 g of plasticizer DIDP into a planetary mixer, dehydrate at 120 °C for 3 h, cool to 50 °C, add 1 g of chain extender BDO, 0.5 g of dibutyltin dilaurate, and 15 g of phosphorus-modified magnesium hydroxide, mix well, heat to 75 °C, react for 4 h, and finally add 10 g of phosphorus-containing diisocyanate and stir to mix well to obtain a high-strength flame-retardant polyurethane structural adhesive.
[0041] Example 5: (1) Add 0.1 mol of iminodipropionic acid and 1.5 mmol of 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add 0.12 mol of diphenylphosphinoyl chloride, add 0.08 mol of triethylamine under nitrogen protection, stir and disperse, heat to 80°C, react for 28 hours, and after the reaction, wash with deionized water, dry, filter, and evaporate to obtain intermediate 1.
[0042] (2) Under nitrogen protection, 80 mmol of intermediate product 1, 192 mmol of epoxybutene and 0.8 mmol of tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 90°C, and reacted for 24 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed with deionized water, and dried to obtain intermediate product 2.
[0043] (3) Add 60 mmol of DOPO to toluene solvent, stir to dissolve, then add 30 mmol of intermediate product 2, heat to 110°C, react for 8 h. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3.
[0044] (4) Add 80 mmol of the intermediate product 3 and 200 mmol of isophorone diisocyanate to N,N-dimethylformamide solvent, stir and mix evenly, heat to 65°C, add 0.6 mmol of dibutyltin dilaurate, and react for 5 h. After the reaction is completed, distill under reduced pressure, wash with deionized water, and dry to obtain phosphorus-containing diisocyanate.
[0045] (5) Under a nitrogen atmosphere, 4 g of dry ultrafine magnesium hydroxide and 12 g of phosphorus-containing diisocyanate were added to a toluene solvent, dispersed by ultrasonication, heated to 80°C, and stirred for reaction for 10 h. After the reaction was completed, the mixture was cooled to room temperature, washed with toluene, and dried to obtain phosphorus-containing modified magnesium hydroxide.
[0046] (6) Add 50 g of castor oil, 10 g of polyether polyol (PPG400), 15 g of polyester polyol (PBA-3000), and 6 g of plasticizer DIDP into a planetary mixer, dehydrate at 120 °C for 3 h, cool to 50 °C, add 1 g of chain extender BDO, 1 g of dibutyltin dilaurate, and 15 g of phosphorus-modified magnesium hydroxide, mix well, heat to 80 °C, react for 3 h, and finally add 15 g of phosphorus-containing diisocyanate, stir and mix well to obtain a high-strength flame-retardant polyurethane structural adhesive.
[0047] Comparative Example 1: The difference between this comparative example and Example 1 is that in step (6), isophorone diisocyanate is used instead of phosphorus-containing diisocyanate.
[0048] Comparative Example 2: The difference between this comparative example and Example 1 is that in step (6), no phosphorus-modified magnesium hydroxide is contained.
[0049] According to GJB446-1988 standard, the 90° peel strength (aluminum / aluminum) was measured using a microcomputer-controlled electronic universal testing machine.
[0050] The polyurethane structural adhesive was cured in an environment of 25°C and 50% relative humidity for 7 days, and the tensile strength was tested according to GB / T528-2009.
[0051] Table 1: Strength test data of polyurethane structural adhesive Peel strength / (N / cm) Tensile strength / MPa Example 1 38.8 9.6 Example 2 43.2 11.0 Example 3 46.9 12.1 Example 4 51.3 15.4 Example 5 48.2 13.1 Comparative Example 1 32.4 7.4 Comparative Example 2 30.1 6.8 It can be seen from the table that the polyurethane structure prepared by the present invention has higher strength.
[0052] Refer to GB / T2408-2008 to test the flame retardant properties of polyurethane structural adhesive.
[0053] Table 2: Flame retardant performance data of polyurethane structural adhesive Flame retardant grade Example 1 V-0 Example 2 V-0 Example 3 V-0 Example 4 V-0 Example 5 V-0 Comparative Example 1 V-1 Comparative Example 2 V-1 It can be seen from the table that the polyurethane structural adhesive prepared by the present invention has a good flame retardant effect, and the organic-inorganic synergistic flame retardant effect is better.
[0054] The present invention uses the above-mentioned embodiments to illustrate the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries and the preparation method, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. High-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries, characterized in that: The polyurethane structural adhesive is composed of the following raw materials in parts by weight: 100 parts by weight of castor oil, 10-30 parts of polyether polyol, 10-30 parts of polyester polyol, 10-20 parts of plasticizer, 2-4 parts of chain extender, 1-3 parts of dibutyltin dilaurate, 10-30 parts of phosphorus-containing modified magnesium hydroxide, and 10-30 parts of phosphorus-containing diisocyanate.
2. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The following steps are involved: S1. Under a nitrogen atmosphere, add dried ultrafine magnesium hydroxide and phosphorus-containing diisocyanate to a toluene solvent, disperse by ultrasonication, heat to 80-90°C, stir and react for 6-10 hours. After the reaction is completed, cool to room temperature, wash with toluene, and dry to obtain phosphorus-containing modified magnesium hydroxide; S2. Add castor oil, polyether polyol, polyester polyol and plasticizer into a planetary mixer, dehydrate at 120°C for 3 hours, cool to 50°C, add chain extender, dibutyltin dilaurate and phosphorus-modified magnesium hydroxide, mix evenly, heat to 70-80°C, react for 2-4 hours, finally add phosphorus-containing diisocyanate, stir and mix evenly to obtain high-strength flame-retardant polyurethane structural adhesive.
3. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 2, characterized in that: In S1, the mass amount of phosphorus-containing diisocyanate is 1.5-3 times the mass amount of superfine magnesium hydroxide.
4. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 2, characterized in that: The preparation method of the phosphorus-containing diisocyanate is: (1) Add iminodipropionic acid and 4-dimethylaminopyridine to chloroform solvent, stir and mix evenly, then add diphenylphosphine chloride, add triethylamine under nitrogen protection, stir and disperse, heat to 70-80°C, react for 20-35h, and after the reaction, wash with deionized water, dry, filter, and rotary evaporate to obtain intermediate 1; (2) Under nitrogen protection, the intermediate product 1, epoxybutene and tetrabutylammonium bromide were added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 80-90°C, reacted for 24-30 hours, and after the reaction was completed, vacuum distilled, washed with deionized water, and dried to obtain the intermediate product 2; (3) Add DOPO to toluene solvent, stir to dissolve, then add intermediate product 2, heat to 100-120°C, react for 6-10 hours, and after the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate product 3; (4) The intermediate product 3 and isophorone diisocyanate are added to N,N-dimethylformamide solvent, stirred and mixed evenly, heated to 60-75° C., and dibutyltin dilaurate is added thereto. The reaction is carried out for 3-6 hours. After the reaction is completed, the product is distilled under reduced pressure, washed with deionized water, and dried to obtain phosphorus-containing diisocyanate.
5. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 4, characterized in that: In the above (1), the molar ratio of iminodipropionic acid to diphenylphosphinyl chloride is 1:1-1.
2.
6. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 4, characterized in that: In the above (2), the molar ratio of the intermediate product 1 to epoxybutene is 1:2-2.
4.
7. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 4, characterized in that: In the above (3), the molar ratio of DOPO to the intermediate product 2 is 2-2.5:
1.
8. The method for preparing the high-strength flame-retardant polyurethane structural adhesive for new energy lithium batteries according to claim 4, characterized in that: In the above (4), the molar ratio of the intermediate product 3 to isophorone diisocyanate is 1:2.2-2.5.
Citation Information
Patent Citations
Vegetable oil-based flame-retardant bi-component polyurethane adhesive and preparation method thereof
CN117106406A
Flame-retardant polyurethane acrylic resin as well as preparation method and application thereof
CN118420874A
Cited By
Flame-retardant modified polyurethane coating and preparation method thereof
CN120059589A